Evaluación de la gestión de recaudación de los impuestos prediales del Gobierno Autónomo Descentralizado Municipal del cantón Chone 2014-2018 - Jama Figueroa, Claudia Beatríz (2021)
The purpose of this research was to evaluate the administrative management for the collection of property taxes carried out by the Municipal Decentralized Autonomous Government of the canton Chone period 2.014- 2.018. In order to achieve the fulfilment of this objective, inductive, deductive and analytical methods were used, those detailing characteristics of the object of study. They were also used such as interviewing for information on administrative processes, services it provides, tax collection, among other aspects. Therefore, management indicators were used, which enabled the application of the traffic light technique to assess the degree of compliance in the taxes collected, where it resulted in demonstrating the lack of management and activities, affecting the recovery of the overdue portfolio of property taxes what generates the lack of income for the implementation of social plans, ultimately once these tools were applied, gave way to the design and implementation of an improvement plan, which contains optimal measures to mitigate deficiencies found in the management of that department, to strengthen management in the area of study.